1990
DOI: 10.1038/bjc.1990.371
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma: infiltrating monocyte/macrophage subpopulations express functional mature phenotype

Abstract: Summary Biopsies from 26 patients with advanced stage squamous cell carcinoma of the head and neck were investigated to determine the intensity of the inflammatory cellular infiltrate and the expression of leucocyte antigens. Mononuclear Tumour growth is influenced by cells and/or products of the tumour's microenvironment. These influences are mainly due to cells of the defence system (Boheim et al., 1987;Kopper & Lapis, 1985;Zeromski et al., 1986;Kabawat et al., 1983). In vitro assays have demonstrated a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…CD4+ cells are primarily located in the tumor stroma, whereas the CD8+ cells are located within the tumor parenchyma 46 . Natural killer (NK) cells, 65 dendritic cells, 68 and macrophages 47,69,70 comprise approximately 5% of the population. Approximately 40% of the T cells present express activation marks of human leukocyte antigen (HLA)‐DR, IL‐2R, or transferrin 71 …”
Section: Discussionmentioning
confidence: 99%
“…CD4+ cells are primarily located in the tumor stroma, whereas the CD8+ cells are located within the tumor parenchyma 46 . Natural killer (NK) cells, 65 dendritic cells, 68 and macrophages 47,69,70 comprise approximately 5% of the population. Approximately 40% of the T cells present express activation marks of human leukocyte antigen (HLA)‐DR, IL‐2R, or transferrin 71 …”
Section: Discussionmentioning
confidence: 99%
“…Many cancers arise from sites of infection, chronic irritation and inflammation (Coussens & Werb, 2002). Among other phenomena, inflammation promotes stromal remodeling and inflammatory cell infiltration (Neuchrist et al, 1990;Ortegel, Staren, Faber, Warren, & Braun, 2000), including monocytes/macrophages, B and T lymphocytes, NK cells, and neutrophils. Our results confirm that tumour progression is accompanied by increased inflammatory cell infiltration, especially macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…There is experimental evidence that the cell-mediated imlnune system plays an important role in the defence against head and neck squamous carcinoma cells [4,8,9,15,22]. Cell-mediated immune functions are executed by T lymphocytes, monocytes, macrophages and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neuchrist et al [15], also using immunohistology, showed that most tumor-infiltrating macrophages are of a functionally mature phenotype. The distribution these authors described is similar to our findings, with an extensive stromal macrophage invasion and some infiltration into the areas of the malignant epithelial cells (with a wide inter-tumoral variation).…”
mentioning
confidence: 99%